Pengembangan Sistem Informasi Monitoring Kinerja Mesin Gilingan Berbasis Android Studi Kasus PG. Krebet Baru II, Malang - Muhammad Hafizh Izzaturrahim; Mochamad Chandra Saputra; Aryo Pinandito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PG Krebet Baru II, Malang is a factory that process sugarcane into sugar that operates for 160 - 180 days each year. The machines work for 24 hours. To keep the machine's performance works optimally, supervisors are responsible to supervising machine's performance to make sure it is in normal condition. The machine's performance data is very dynamic that change in seconds. It means the machine's performance is possible for being abnormal condition only for a few minutes or even in seconds. Currently, the factory has system to monitoring the machine's performance that are connected to application, so it can be opened in mobile device. Unfortunately, the information is passive. It means supervisor won't know any information if they didn't open the system. If the machine's performance is in abnormal condition and the machine is not being watched, it can interfere the machine in the future. From this problem, information system of milling machine should be developed based on Android using push notification features. Supervisor will get notification if the machine's performance is in abnormal condition. Information system of milling machine is developed using waterfall model. The testing in this system use validation testing, user acceptance testing, and basis path testing, where the result of user acceptancce testing conlude that system is valid and compatible with user requirements and the basis path testing conclude that the largest cyclomatic complexity is 17.